Effect of Using Flashcards with Active Recall Method On 3rd Grade Students’ Vocabulary Mastery at MI Mambaul Ulum Dahu Kediri - Alam, Muhammad Izzul; Suhartono; Susanti, Yunik (Proceeding International Conference on Education, 2025)
This study aims to investigate the effectiveness of flashcards combined with the active recall method in improving the English vocabulary mastery of elementary school students. The research was conducted using a quantitative approach with a pre-experimental design, specifically the one-group pre-test and post-test design. A group of students was given a vocabulary pre-test, followed by several sessions using flashcards and active recall activities, and then assessed with a post-test. The data were analyzed using the Wilcoxon Signed-Rank Test to determine the significance of differences between pre-test and post-test scores. The results showed a notable improvement in students’ vocabulary mastery after the intervention, particularly in pronunciation, recognition, and the ability to use words in context. While most students experienced progress, some showed little to no change, and a few had a slight decline, indicating varying levels of effectiveness. A t-test analysis is also considered as a comparative method to support the findings. The study suggests that incorporating memory-based and interactive methods such as flashcards and active recall can enhance vocabulary learning more effectively than traditional approaches. These results highlight the importance of engaging techniques in primary English education.